Error Analysis Found in Students’ Narrative Text Writing: A Study at the Tenth Grade Students of SMAN 4 Kota Serang - Terenovix, Salzha; Handayani, Rita; Irawati, Tita; Permana, Muhammad Bayu Heri; Habibaturosyi'ah, Nurul (Jurnal Kajian Ilmu Pendidikan (JKIP), 2023)
Mastering the four basic English skills, particularly writing, is crucial for effective communication. However, numerous EFL students in Indonesia encounter challenges due to the disparities in language structure, grammar, and language style between Bahasa Indonesia and English. These challenges can lead to difficulties in constructing sentences and applying correct tenses, resulting in grammatical errors. This study investigates grammatical errors in students' narrative text writing, focusing on grammar, spelling, punctuation, and capitalization. Both qualitative and quantitative methods were employed in this study. There were 10 students from the X MIPA 3 class at SMAN 4 Kota Serang involved as the participants in this study. The data were collected through document analysis and interviews. The result showed that there were 67 errors found in students’ writing narrative composition which were classified into four categories: (1) 39 grammar errors (50.64%), (2) 2 spelling errors (2.59%) (3) 15 punctuation errors (19.48%), and (4) 21 capitalization errors (27.27%). The factors that contributed to students' writing difficulties include: (1) a lack of understanding of the learning materials, (2) difficulty in generating ideas during the writing process, and (3) unfamiliarity with English grammar and vocabulary. The students address these challenges by seeking for information from the internet, books, and friends.